Onset risk and draft animal investment in Nigeria - Takeshima, Hiroyuki (International Food Policy Research Institute, 2012)
Onset risk, the uncertainty in the onset of rainy season, is an important element of weather risk for African farmers with little access to formal insurance who engage in traditional rainfed farming. A knowledge gap still exists empirically on how onset risk may affect the investment decisions of these farmers. In particular, farm productivity in Africa still depends on substantial labor inputs at the onset of the rainy season, sometimes involving seasonal migration to rural areas. With credit and insurance market failure, poor access to weather-related information, and high labor mobility costs, high and increasing onset risk may affect farmers’ demand for farm mechanization. We test this hypothesis by investigating the effect of onset risk on farmers’ investment in draft animals in northern and central Nigeria. We use the example of a public project providing farmers with financial support for the acquisition of productive assets. We calculate the onset of the rainy season using daily rainfall data in various locations across Nigeria and identify locations that have experienced increasing, decreasing, or constant onset risk in the past few decades. We then exploit the panel structure of our dataset and employ stratified propensity score matching to estimate the average treatment effect on the treated, differentiated by the onset risk and its change. The results support our hypothesis. Farmers in areas with higher, increasing, or constant onset risk were more likely to invest in draft animals, and such effects are clearer among larger-scale farmers. Linkages are also clearer with onset risk compared to annual rainfall risk.